Building on the anti-PD1/PD-L1 backbone: combination immunotherapy for cancer. (3rd August 2019) - Ingles Garces, Alvaro H; Au, Lewis; Mason, Robert; Thomas, Jennifer; Larkin, James
ABSTRACT: Introduction : Immunotherapy has revolutionized the treatment of cancer. Given this growing success, at the same time, there are significant limitations and unanswered questions concerning response rates, duration of therapy, why some patients respond and others do not, and if combining different immune-agents would overcome this lack of response, increase the chance of success and postpone acquired resistance. Areas covered : The comprehension of how to properly modulate the immune pathways, the molecular and the immunological bases of the disease, will be fundamental to guide the development of therapeutic interventions and combinations that will be more suitable for treatment of cancer patients. In this review, we discuss the strategies of immunotherapy combinations in order to develop more effective immunotherapy programs, with a particular focus on melanoma and renal cancer patients, as well as the combination of immunotherapy and chemotherapy. Expert Opinion : Given the complexity of immune activation, combinatorial approaches are needed, and due to the considerable variability in tumor biology across patients and tumor types, patient selection and biomarkers need to be further explored. In summary, combined therapies have shown promising success, but additional and continuous research to identify the safety, efficacy, optimal combination, dosage and timing are still required.